2006
DOI: 10.1007/s10593-006-0200-5
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-quinolones. 107. Reaction of triethyl methanetricarboxylate with indoline

Abstract: Keywords: amides of 4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acids, heterocyclic derivatives of tricarbonylmethane, ethyl esters, X-ray structural analysis, thermolysis.The condensation of N-substituted anilines with a double or triple excess of methanetricarboxylic acid triethyl ester is used as one of the variants of the synthesis of ethyl esters of 1-substituted 4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acids [2,3]. We have shown in the example of indoline [4] and diphenylamine [5] that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Since these occur in the unassigned spectrum at 90.23 and 159.90 ppm the first must be the C (3) carbon atom and the second C (2) . 735 The 13 C NMR spectra of esters 1a-e also proved to be similar and a detailed study showed that the C (2) and C (9) signals had a width 3-4 time greater than the width of the remainder. These signals correspond to the carbon atoms placed close to the N (1) atom.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Since these occur in the unassigned spectrum at 90.23 and 159.90 ppm the first must be the C (3) carbon atom and the second C (2) . 735 The 13 C NMR spectra of esters 1a-e also proved to be similar and a detailed study showed that the C (2) and C (9) signals had a width 3-4 time greater than the width of the remainder. These signals correspond to the carbon atoms placed close to the N (1) atom.…”
mentioning
confidence: 85%
“…It was not possible to avoid formation of pyridyl-2-amide 3a in any of the experiments. However, this is a direct result of the direct amidation of the initially formed heterocyclic ester 1a by 2-aminopyridine since, in the first place amide 3a is separated even when carrying out the reaction in the comparatively low boiling toluene and, in the second, a thermal intramolecular cyclization of the intermediate ethyl bis(pyridin-2-ylcarbamoyl)acetate needs much more forcing conditions [9]. None the less, exchange of bromobenzene for xylene leads to some increase in the yield of the target ester 1a and simultaneous lowering of the amount of the unwanted pyridyl-2-amide 3a.…”
mentioning
confidence: 99%
“…However, the presence of a more powerful nucleophile in the structure of this intermediate (the bipolar 1,4-dihydro form 13, whose formation from 4-hydroxy-2-quinolinones has been noted by us before [8,9]) leads to the fact that the reaction finishes with heterocyclization. The significant factors responsible for such a reaction course are undoubtedly the size of the ring formed and the extreme convenience of the spatial positioning of the two reaction centers for its closing.…”
mentioning
confidence: 95%
“…Сейчас найдено, что лучшие результаты могут быть достигнуты при использовании триэтилметантрикарбокси-лата в качестве ацилирующего и конденсирующе-го агента, а также высококипящего теплоноси-теля одновременно, что позволяет не только зна-чительно упростить его регенерацию, но и прак-тически полностью избежать нежелательного обра-зования 2-гидрокси-4-оксо-N-(пиридин-2-ил)-4Н-пиридо[1,2-а]пиримидин-3-карбоксамидов. Для подавления побочных реакций важен также и порядок введения исходных веществ в реакцию: вместо обычного постепенного нагревания ре-акционной смеси с последующим ее кипячени-ем, способствующим формированию триамидов метантрикарбоновой кислоты [23], следует к уже горячему триэтилметантрикарбоксилату прибав-лять раствор аминопиридина в триэтилметан-трикарбоксилате. На примере синтеза этилово-го эфира 2-гидрокси-8-метил-4-оксо-4Н-пиридо [1,2-а]пиримидин-3-карбоновой кислоты (1) по-казано, что такая несложная в исполнении моди-фикация позволяет получать целевой продукт с более высоким выходом и чистотой.…”
Section: Issn 2308-8303unclassified